Produção artesanal : análise do método de intervenção de design no artesanato potiguar sob o ponto de vista dos atores envolvidos no processo - Leal, Marijara de Lourdes (2011)
This work presents an analysis of the method of intervention used in the craft of design by SEBRAE in Rio Grande do Norte under the viewpoint of the actors involved, especially the craftsmen and design consultants. The research methodology used was based on the ergonomic work analysis - AET, applying observational techniques and interactive. Data tabulated from the matrix to include comments were analyzed in order to allow the generation of qualitative and quantitative information. The results of this research allow us to affirm that for the process of innovation through the design of intervention are satisfactory for all involved, it is necessary that the bonds of interaction are established and the joint actions in the innovation process to bear fruit in favor sustainability of artisan groups